2003
DOI: 10.1002/zaac.200390151
|View full text |Cite
|
Sign up to set email alerts
|

Oligonary Nitrides and Oxonitrides of Si, P, Al, and B in Combination with Rare Earth or Transition Metals as well as Molecular Precursor Compounds with Nitrido Bridges M‐N‐Si (M = Ti, Zr, Hf, W, Sn)

Abstract: A novel synthetic approach is presented leading to hitherto unknown nitridosilicates, oxonitridosilicates, oxonitridoaluminosilicates, carbidonitridosilicates, as well as nitridoborates and oxonitridoborates of rare earth elements, alkali, and alkaline earth metals. Typically, the respective metals were reacted with silicon diimide, aluminum nitride, or poly(boron amide imide), respectively, under pure nitrogen atmosphere utilizing a radiofrequency furnace. Usually, the compounds are obtained within short reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Characterization and thermal degradation of the latter yielding nanocrystalline LnN solids has recently been reported. [10,11] Partial substitution of O by N in lanthanide-containing Si/ N materials (nitridosilicates) [12][13][14] allowed tailor-made tuning of luminescent properties for industrial application of these Abstract: We present two organometallic precursor approaches leading to the hitherto-unknown dioxo monocarbodiimides (Ln 2 O 2 CN 2 ) of the late lanthanides Ho, Er, and Yb as well as yttrium. One involves insertion of CO 2 , and the other one is a straightforward route using a molecular single-source precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Characterization and thermal degradation of the latter yielding nanocrystalline LnN solids has recently been reported. [10,11] Partial substitution of O by N in lanthanide-containing Si/ N materials (nitridosilicates) [12][13][14] allowed tailor-made tuning of luminescent properties for industrial application of these Abstract: We present two organometallic precursor approaches leading to the hitherto-unknown dioxo monocarbodiimides (Ln 2 O 2 CN 2 ) of the late lanthanides Ho, Er, and Yb as well as yttrium. One involves insertion of CO 2 , and the other one is a straightforward route using a molecular single-source precursor.…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, only a few successful synthetic approaches known for the synthesis of such simple compounds with defined composition. Our general interest to target new nitride containing materials with molecular-precursor syntheses, [27,28] led us to utilize organolanthanide molecular precursors for solid-state synthesis of highly activated rare earth nitrido compounds (Scheme 1). On this background molecular precursor compounds with ligands exhibiting an adequate thermal lability for subsequent pyrolysis reactions were targeted.…”
Section: Reactive Lanthanide Nitride Materialsmentioning
confidence: 99%
“…Research previously carried out in our laboratory revealed that the introduction of oxygen into Ln nitridosilicates results in interesting luminescent properties. [13][14][15][16][17] The CO 2 reactivity studies of these precursor compounds reported herein enlarge the potential of amorphous O/C/N-containing solids as future reagents for materials science.…”
Section: Introductionmentioning
confidence: 99%